Storm and conquest the battle for the Indian Ocean, 1809 - Taylor, Stephen 1949- (Faber, 2007)
An account of maritime losses in the Indian Ocean in 1808 and 1809, in which fourteen East Indiamen carrying saltpetre for the Peninsular campaign were lost to a combination of storms, shipwreck and enemy action.
Keywords: Geschichte 1800-1900; Geschichte; Napoleonic Wars, 1800-1815 -- Campaigns -- Indian Ocean; Frankreich; Großbritannien; France -- History, Naval -- 19th century; Great Britain -- History, Naval -- 19th century; Indian Ocean -- Strategic aspects -- History -- 19th century; Mauritius -- History -- To 1810